Digital Integration and Legal Innovation in Qashqadaryo Folk Crafts: Integrasi Digital dan Inovasi Hukum dalam Kerajinan Rakyat Qashqadaryo - Norqobilova Feruza Abduhomidovna (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Folk crafts are a vital component of Uzbekistan’s national heritage and an important sector for regional socio-economic development. Specific Background: In the Qashqadaryo region, there is a growing movement to integrate traditional handicrafts with modern digital technologies and intellectual property (IP) frameworks. Knowledge Gap: However, few studies have examined how digital tools like 3D modeling and IoT are being practically applied in crafts, and how artisans interact with patenting systems. Aims: This study investigates the synergetic modernization of folk crafts through digitalization and IP protection to enhance production efficiency, design innovation, and market competitiveness. Results: Field data, trend modeling, and correlation analysis reveal systemic barriers such as low digital literacy, limited IP awareness, and insufficient infrastructure. Nevertheless, emerging initiatives—such as regional innovation hubs and blockchain-based IP systems—demonstrate growing institutional support. Novelty: The paper introduces a holistic “synergistic approach” combining digital design, smart production, and legal safeguards, tailored to the cultural and economic context of Uzbek artisans. Implications: Findings support the creation of targeted policies and educational programs, positioning folk crafts within the digital economy and ensuring their sustainable, legally protected development in global markets.Highlight : Digital Integration: Introducing 3D modeling and IoT boosts production efficiency and design quality in traditional crafts. Legal Protection: Patenting crafts as intellectual property strengthens ownership and market competitiveness. Regional Empowerment: Innovation hubs and artisan training improve skills, preserve heritage, and drive local economies. Keywords : Folk Crafts, Digital Technology, Intellectual Property, Patenting, Innovation